Prevalência da disfunção das glândulas de meibomius e suas comorbidades, em pacientes com lipodistrofia generalizada congênita - Gomes, Lorena Maria Araújo (2019)
Introduction: The Meibomius glands are responsible for the oily layer of the tear, providing stability to the tear film and promoting the health of the ocular surface. Meibomius gland dysfunction (MGD) is the main cause of evaporative dry eye, leading to a decrease in the quality of life of the affected patients. Recently, the association of dyslipidemia and diabetes in the pathophysiology of this dysfunction has been speculated. Congenital generalized lipodystrophy (CGL) is characterized by early insulin resistance and dyslipidemia, which can be found in the first years of the life of patients. There are no studies on the ophthalmologic alterations in patients with this syndrome and the evaluation of these can allow a correlation between these pathologies, removing the bias of age. Objectives: To evaluate the prevalence of MGD and its comorbidities in patients with CGL. Methods: This is a cross-sectional study performed at the Ophthalmology outpatient clinic of Walter Cantídio University Hospital. Patients with a clinical or genetic diagnosis of CGL were included. The patients were submitted to a medical interview, visual acuity examination, anterior segment evaluation in the slit lamp with lacrimal film and ocular surface evaluations, retinal mapping and fasting blood samples for glucose, basal insulin, total cholesterol, HDL cholesterol, and triglycerides. HOMA-IR and LDL cholesterol were calculated. Fisher’s exact test, Mann-Whitney, Spearman correlation, Program: Stata 13. Significant p < 0.05. Continuous quantitative variables were described in median (minimum and maximum); and qualitative ones, by proportions. Results: Eighteen patients with a diagnosis of CGL were included, the median age was 11.5 years (2 to 32), of which 12 (66.7%) were younger than 19 years. In relation to sex, 12/18 (66.7%) were women. All patients were dyslipidemic: 83.3% (15/18) had hypertriglyceridemia, 94.4% (17/18) low HDL-cholesterol levels and 38.9% (7/18) increase in total cholesterol. Regarding the glycemic profile, 66.7% were diabetic and non-diabetic, 33.3% (2/6) had already increased values of HOMA-IR. The prevalence of low visual acuity was 6.2% (2/32 eyes). In biomicroscopy, 77.7% (14/18) patients with MGD were diagnosed. Of these, all presented a decrease in tear film rupture time and 50% (7/15) presented some degree of ocular surface impairment. There was a higher prevalence of patients with diabetes and hypertriglyceridemia among patients with MGD. There was also a statistically significant difference between HOMA-IR values among diabetic patients with MGD associated with ocular surface alteration, and a trend towards higher values of glycated hemoglobin in this group. Conclusion: There was a high prevalence of MGD in patients with CGL, especially in diabetics and with hypertriglyceridemia. In addition, there was a prevalence of patients with increased levels of insulin resistance and glycemic control among those with MGD associated with ocular surface alteration. These data reinforce the hypothesis of the relationship between dyslipidemia and diabetes in the pathophysiology of MGD.